ANALISIS KINERJA KEUANGAN PT. â€œAâ€ INDONESIA TAHUN 2007 â€“ 2012 - Utami, Chairina; hir, Djuma (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study aims to identify and analyze financial performance of PT. Â â€œAâ€ Â Indonesia inÂ 2007 - 2012 assessed by the ratio of liquidity, solvency, profitability, and activity. Â This study is a descriptive analysis research by using a quantitative approach. This studyÂ uses quantitative data as the only type of data. Based on the source, the data used in this study isÂ primary data, the data obtained directly from the PT.